Leisure and Recreation Management - Torkildsen, George (London : Routledge, 2005)
'Leisure and Recreation Management' is essential reading for anyone interested in exploring both the theory and the practicalities of managing leisure and recreational facilities.
Previous ed.: London: Spon, 1999.
Includes bibliographical references (p. 563-575) and index.
Keywords: Leisure industry -- Great Britain -- Management; Recreation -- Great Britain -- Management; Performing Arts